Predicting Aspergillus fumigatus exposure from composting facilities using a dispersion model: a conditional calibration and validation - Douglas, Philippa; Tyrrel, Sean F.; Kinnersley, Robert P.; Whelan, Michael J.; Longhurst, Philip J.; Hansell, Anna L.; Walsh, Kerry A.; Pollard, Simon J. T.; Drew, Gillian H. (Elsevier, 2017)
Bioaerosols are released in elevated quantities from composting facilities and are associated with negative health effects, although dose-response relationships are unclear. Exposure levels are difficult to quantify as established sampling methods are costly, time-consuming and current data provide limited temporal and spatial information. Confidence in dispersion model outputs in this context would be advantageous to provide a more detailed exposure assessment. We present the calibration and validation of a recognised atmospheric dispersion model (ADMS) for bioaerosol exposure assessments. The model was calibrated by a trial and error optimisation of observed Aspergillus fumigatus concentrations at different locations around a composting site. Validation was performed using a second dataset of measured concentrations for a different site. The best fit between modelled and measured data was achieved when emissions were represented as a single area source, with a temperature of 29 °C. Predicted bioaerosol concentrations were within an order of magnitude of measured values (1000–10,000 CFU/m3) at the validation site, once minor adjustments were made to reflect local differences between the sites (r2 > 0.7 at 150, 300, 500 and 600 m downwind of source). Results suggest that calibrated dispersion modelling can be applied to make reasonable predictions of bioaerosol exposures at multiple sites and may be used to inform site regulation and operational management.
Keywords: Compost; Bioaerosol; Aspergillus fumigatus; ADMS; Calibration; Validation